Pengeringan Umbi Porang Menggunakan Alat Pengering Hybrid Tipe Rak TETA-FAR21 - Afwan Munadi; Longdong, Ireine A.; Lengkey, Lady CH. E.; Tooy, Dedie; Ludong, Daniel P. M.; Syahrir, Risal N. R. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2025)
This study aims to analyze the performance of the TETA-FAR21 hybrid rack-type dryer in the drying process of Amorphophallus muelleri (porang) tubers. The research focuses on observing temperature, relative humidity, drying efficiency, and the drying characteristics, including the relationship between moisture content and drying rate over time. The study was conducted at the Biosystems Engineering Laboratory, Postharvest Subdivision, Faculty of Agriculture, Sam Ratulangi University, using an experimental method. The dryer consists of two racks, each containing six sample trays of approximately 100 g, with slice thickness treatments of 3 mm and 4 mm. The results showed that the average solar radiation intensity for the 3 mm thickness treatment was 476.1 W/m², while for 4 mm it was 372.4 W/m². The drying efficiency reached 7.32% for the 3 mm thickness and 6.19% for the 4 mm thickness. The hybrid dryer effectively maintained a stable temperature of 55°C. The moisture content of porang tubers decreased from 88.48% to 12.21% within 25 hours for the 3 mm slices and to 12.86% within 26 hours for the 4 mm slices. The average drying rate was 3.06%/hour for the 3 mm slices and 2.90%/hour for the 4 mm slices. Overall, the TETA-FAR21 hybrid dryer demonstrated efficient performance in maintaining stable drying conditions and producing high-quality dried porang chips.